Pemerolehan Bahasa Pertama Anak Usia Dini dalam Perspektif Psikolinguistik dan Implikasinya bagi Pendidikan Bahasa Indonesia - Tuti Wahyuni; Diva Yuwantika; Fatmawati F (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The study analyzes the process of first language acquisition in early childhood from a psycholinguistic perspective with a focus on neurological cognitive foundations and language disorders in Indonesian language education, identifying key neural mechanisms, inhibiting factors, and recommendations for pedagogical interventions. A qualitative approach with an interpretive paradigm is used through literature studies from psycholinguistics, child neurology, and Indonesian language education journals, analyzed following the Miles and Huberman model which includes thematic data reduction, matrix and diagram presentation, and triangulation for conclusions. Major neurological mechanisms include Broca's activation for speech production, Wernicke's for semantic comprehension, as well as high synaptic plasticity that processes Indonesian phonemes from babbling to complex sentences at the age of 0-6 years, supported by Chomsky's Universal Grammar theory and connectionist models. Disorders such as speech delay, expressive-receptive language, articulatory phonological, pragmatic autism, and stuttering disrupt the cortico-striatal and prefrontal cortex pathways, leading to limitations in vocabulary, syntax, and social interaction. Integration into the Indonesian education curriculum through sensory stimulation modules, NLP exercises, motor games, singing rhythms, and neuroimaging-based teacher training restores neural connections, accelerates lexicon milestones, and forms an inclusive ecosystem with continuous evaluation via observation and biofeedback.